Synthesis Roller Cam Drive Mechanism Molding Installation with Combined Mode Movement Acceleration Fourth Order - Loveikin, V.; Pochka, К.; Loveikin, Yu. (Polish Academy of Sciences, 2018)
For the purpose of increase in reliability and durability of roller forming installation the optimum mode of back and forth motion of the forming cart on acceleration of the fourth order is calculated.
Синтез кулачкового приводного механизма роликовой формовочной установки с комбинированным режимом движения по ускорению четвёртого порядка
Keywords: roller forming installation; mode of movement; step engine; drive; роликовые формовочные установки; режим движения; шаг двигателя; привод